Alkoxyphenylthiophene Linked Benzodithiophene Based Medium Band Gap Polymers for Organic Photovoltaics: Efficiency Improvement upon Methanol Treatment Depends on the Planarity of Backbone - Kranthiraja, Kakaraparthi; Gunasekar, Kumarasamy; Cho, Woosum; Song, Myungkwan; Park, Young Geun; Lee, Jin Yong; Shin, Yurim; Kang, In-Nam; Kim, Ajeong; Kim, Hyunjung; Kim, BongSoo; Jin, Sung-Ho (AMER CHEMICAL SOC, 2014)
Two donoracceptor (DA) medium band gap polymers, P1 and P2, alkoxyphenylthiophene (APTh) linked benzodithiophene (BDT) as an electron-rich unit and 1,3-di(2'-bromothien-5'-yl)-5-(2-ethylhexyl)thieno[3,4-c]pyrrole-4,6-dione (TPD) (A1) or [5,6-bis(octyloxy)-4,7-di(thiophen-2-yl)benzo[c][1,2,5]thiadiazole] (BT) (A2) as an electron-deficient unit, have successfully been synthesized via microwave-assisted Stille polymerization and utilized for bulk heterojunction (BHJ) polymer solar cells (PSCs). P1 shows a well-distinguished absorption shoulder between 590 and 620 nm attributed to the pi-pi stacking of a polymer backbone; such kind of absorption shoulder is not observed in P2, indicating that the P1 has more planar structure than that of P2. This is due to the fact that the sulfur atom of thiophene spacer and the oxygen atom of carbonyl groups in TPD have more pronounced intramolecular noncovalent interactions (INCI) in P1 than that of the sulfur atom of thiophene spacer and the oxygen atom of alkoxy groups of BT in P2. The bulk heterojunction polymer solar cells (BHJ PSCs) were fabricated with the configuration of ITO/PEDOT:PSS/polymer (P1 or P2):PC71BM/LiF/Al. The P1 device shows better photovoltaic performance with open-circuit voltage (V-oc) of 0.91 V and the power conversion efficiency (PCE) of 4.19% than the P2 device (V-oc: 0.71 V; PCE: 1.88%) in neat blend films under the illumination of AM 1.5G (100 mW/cm(2)). Upon treating the active layers containing P1 and P2 with methanol, the PCE of the P1 device is increased from 4.19 to 7.14%. In contrast, the PCE of the P2 device is decreased from 1.88 to 1.82%. Space charge limited current mobility, atomic force microscopy, transmission electron microscopy, time-of-flight secondary ion mass spectrometry, and impedance spectroscopy studies strongly support the enhanced PCE for the P1 device is attributed to the increased mobility, nanoscale morphology, and reduced resistance upon methanol treatment; these favorable properties for the P1 polymer are highly correlated with the planarity of the backbone.
Keywords: POWER CONVERSION EFFICIENCY; HETEROJUNCTION SOLAR-CELLS; OPEN-CIRCUIT VOLTAGE; BULK-HETEROJUNCTION; CONJUGATED POLYMERS; MOLECULAR DESIGN; BUILDING-BLOCK; PERFORMANCE; COPOLYMERS; ENHANCEMENT